Externalization of the Italy-Albania Protocol on Extraterritorial Migration and Asylum Management Toward the Handling of Asylum Seekers in Indonesia - Rustam, Olivia Alvionita; Erawaty, Rika; Grizelda, Grizelda (Faculty of Law, Universitas Jambi, 2025)
Background: The surge in migration to Europe, particularly to Italy, has prompted bilateral cooperation with Albania through the Italy-Albania Protocol on Extraterritorial Migration and Asylum Management. This protocol aims to reduce Italy’s burden by transferring the asylum status determination process to facilities in Albania. Meanwhile, Indonesia faces challenges related to Rohingya refugees fleeing persecution in Myanmar, making it a transit country for those seeking protection. This study aims to analyze the legality of the Italy-Albania Protocol in the context of fulfilling the human rights of asylum seekers and explore the application of the concept of externalization of asylum control from the protocol in Indonesia to address the Rohingya issue. The method used is doctrinal research with a legislative and comparative approach, as well as an analysis of international legal instruments such as the Universal Declaration of Human Rights and the 1951 Refugee Convention. The results of the study indicate that the substance of the articles in the Italian-Albanian protocol does not explicitly violate human rights and is in line with international principles. The externalization of asylum control is recognized as a global strategy to reduce migration pressure. However, Indonesia faces limitations in facilities, human rights violations, and the lack of ratification of the 1951 Refugee Convention, while Presidential Regulation No. 125 of 2016 has not been optimal in guaranteeing the rights of asylum seekers. Therefore, international cooperation and ASEAN synergy are essential for responsibility-sharing, improving facilities, and public education to support humanitarian principles and compliance with international law.